The Effect of Financial Literature and Financial Technology on Financial Inclusion Among Accounting Student - Dhany Efita Sari; Erlin Ade Selviana; Brilliani; Nadia Fauzi Asila; Miftakhul Jannah (International Journal of Social Science and Business, 2022)
Improvements in financial literacy serve as the primary driver of financial inclusion. To avoid financial difficulties, everyone should be financially literate. Having better financial literacy increases one's chances of enjoying life's pleasures while also being well-funded. This study aims to analyze the effect of financial literacy and financial technology on financial inclusion. The population in this study consisted of 180 accounting students. This study was a causal comparative research, and the data collection method used was a cross-sectional survey with proportional stratified random sampling. The Krejcie and Morgan table was used to determine the research sample of up to 123 students. According to the findings, financial literacy has a positive and significant impact on financial inclusion. Furthermore, financial technology has a significant and positive impact on financial inclusion. And, simultaneously, financial literacy and financial technology have a positive and significant impact on financial inclusion. If financial literacy and financial technology are increasing factors, it is recommended that the government consider these aspects if you want to increase financial inclusion among students. Other variables from financial inclusion instruments can be added for further research by collecting samples from several universities in various regions.